Two new littoral species of the genus Anurida Laboulbène, 1865 (Collembola, Neanuridae) from the Pacific coast of Asia - Babenko, Anatoly; Nakamori, Taizo (Zootaxa, 2018)
Two new littoral species of the genus Anurida, viz. A. kyshyensis sp. nov. and A. abashiriensis sp. nov., have been described from the eastern coasts of Chukchi Peninsula (Russia) and Hokkaido Island (Japan), respectively. The former species is most similar to sympatric A. similis Fjellberg, 1985 and A. martynovae Fjellberg, 1985 differing from both of them due to the permanent presence of additional lateral setae on thorax and 3+3 axial setae on Abd.4. A. abashiriensis sp. nov., having unique mandibles and hypertrophic elongate maxillae with long lamellae, is hard to compare with any known species of Anurida and allied genera.